Factors driving the variation in soil fertility associated with extension of the alfalfa (Medicago sativa L.) cultivation period - Zeyu Liu; Junqi Wang; Xinhe Shan; Pinhang Liang; Lizhao Fan; Chengyu Song; Zhaopu Jia; Yuxia Zhang; Yunlong Zhang; Lei Liu; Ding Huang (Soil Advances)
Intensive agricultural practices and prolonged monoculture of alfalfa (Medicago sativa L.) have significantly compromised soil health, highlighting the urgent need to investigate cultivation duration thresholds and their underlying determinants to optimize soil fertility management. To address this gap, four alfalfa fields with different planting years (0, 1, 2, 4) were selected at Henan province in China, to investigate the pattern of soil physicochemical, microbial properties in topsoil (0–20 cm) and subsoil (20–40 cm). The results indicated that soil organic carbon (SOC), total nitrogen (TN), available phosphorus (AP), and available potassium (AK) in topsoil were significantly increased with the extension of years (P < 0.05). In topsoil, soil macro-aggregates and the mean weight diameter (MWD) showed an initial decrease and then a gradual increase with the number of planting years. In contrast, soil micro-aggregates, and middle-aggregates increased initially and then decreased. In subsoil, there were no significant differences with respect to the number of planting years, with the exception of micro-aggregates that showed the lowest values in the fourth year. Both total and fungal microbial biomass showed increase trend with planting year in topsoil, with no change in subsoil. The soil health index (SHI) showed decline and then increase with the extension of planting years and reached maximum value 0.74 in the fourth year in topsoil. In subsoil, SHI showed decline at 1st year, and then increased at 2nd year and finally stabilized in the fourth year. Our results suggested that the impacts of planting years on soil fertility in topsoil were more pronounced than those in subsoil, which both primarily driven by SOC, followed by TN. In our filed experiment with less than 5-year, alfalfa plant for a period of 4 years was optimal for soil fertility improvement especially in topsoil. These findings underscore the effects of continuous alfalfa cultivation on soil physicochemical, microbial properties and functional contributions to soil health in Henan Province. This study could provide insights for policy makers for the effective management and sustainable development of alfalfa production.